APPLYING KNOW â WANT â LEARN (KWL) STRATEGY ON TEACHING READING COMPREHENSION - Rahmasari, Brigitta Septarini; Amumpuni, Rengganis Siwi (English Teaching Journal, 2014)
Over the last few decades, many instructors have been trying all kinds of teaching methods, but without benefit. Nevertheless, in the 1986, a new technique is appeared which called K-W-L technique. It is specified for reading comprehension passages because reading skill is not easy matter for students. Therefore, the K-W-L technique is a good one for thinking and experiences. The outcomes of present research appeared that K-W-L enables the students to activate their prior knowledge and operate their thinking.